1996
DOI: 10.1007/s002800051031
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of interleukin 12 in preclinical models

Abstract: Interleukin 12 (IL-12) is a heterodimeric cytokine with a number of biological effects that are consistent with its potential role as an antitumor agent. The antimetastatic and antitumor activities of IL-12 have been demonstrated in a number of murine tumor models. Both the inhibition of established experimental pulmonary or hepatic metastases and a reduction in spontaneous metastases have been achieved by treatment with murine IL-12. Systemic treatment of mice bearing subcutaneous tumors with IL-12 results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 0 publications
0
49
2
Order By: Relevance
“…First-strand cDNA was prepared using the first-strand cDNA synthesis kit (Life Technologies) according to the manufacturer's instructions; however random hexamer primers at 10 ng/ L (Amersham Pharmacia Biotech, Orsay, France) were substituted for oligo(dT) [12][13][14][15][16][17][18] .…”
Section: Vectors and Retroviral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…First-strand cDNA was prepared using the first-strand cDNA synthesis kit (Life Technologies) according to the manufacturer's instructions; however random hexamer primers at 10 ng/ L (Amersham Pharmacia Biotech, Orsay, France) were substituted for oligo(dT) [12][13][14][15][16][17][18] .…”
Section: Vectors and Retroviral Infectionsmentioning
confidence: 99%
“…Animal studies have revealed that IL-12 has powerful antitumoral, antimetastatic, and anti-angiogenic activities. [15][16][17][18] This potent antitumoral effect of IL-12 seems to depend upon stimulation of the immune system via direct activation of antitumoral natural killer cells and T lymphocytes, which express specific IL-12 receptors. 19,20 An important indirect mechanism of action is provided by the resulting secretion of interferon-␥ by these cells, which increases antigen presentation [21][22][23] and induces tertiary secretion of anti-angiogenic factors.…”
mentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30] IL-2 is the primary cytokine responsible for the activation and clonal expansion of CD8 ϩ cytotoxic T lymphocytes (CTLs), which are the primary effector cells that target tumors in an antigen-specific manner. 2 IL-12 functions to activate and clonally expand natural killer (NK) cells, which kill tumors in a major histocompatibility complex (MHC)-independent fashion.…”
mentioning
confidence: 99%
“…IL-12 is a cytokine that mediates the T H 1-type immune response, stimulates natural killer (NK) cell activity, and has also been shown to have antiangiogenic properties [24][25][26] It has known antitumor properties in a variety of models. 25,27 We have previously demonstrated that a g 1 34.5-deleted HSV-1 expressing murine IL-12 (M002) prolonged survival of immunocompetent mice in an experimental intracranial murine model of neuroblastoma. 28 Recently, combinatorial cytokine therapy has been pursued in a wide array of cancer therapies.…”
mentioning
confidence: 99%
“…IL-12 has been shown to have increased antitumor effects when used in combination with additional cytokines. 27 Because of its ability to stimulate chemotaxis of monocytes and numerous T-lymphocyte subsets, monocyte chemoattractant protein-1 (MCP-1), now called CCL2, is potentially a good candidate for increasing the antitumor effects of IL-12. CCL2 is a member of the C-C chemokine family and stimulates chemotaxis of monocytes, CD4 þ and CD8 þ , memory T lymphocytes and dendritic cells in vitro.…”
mentioning
confidence: 99%